Overexpression of the Transcription Factor GROWTH-REGULATING FACTOR5 Improves Transformation of Dicot and Monocot Species - Kong, Jixiang; Martin-Ortigosa, Susana; Finer, John; Orchard, Nuananong; Gunadi, Andika; Batts, Lou Ann; Thakare, Dhiraj; Rush, Bradford; Schmitz, Oliver; Stuiver, Maarten; Olhoft, Paula; Pacheco-Villalobos, David (Frontiers in Plant Science, 2020)
Successful regeneration of genetically modified plants from cell culture is highly dependent on the species, genotype, and tissue-type being targeted for transformation. Studies in some plant species have shown that when expression is altered, some genes regulating developmental processes are capable of triggering plant regeneration in a variety of plant cells and tissue-types previously identified as being recalcitrant to regeneration. In the present research, we report that developmental genes encoding GROWTH-REGULATING FACTORS positively enhance regeneration and transformation in both monocot and dicot species. In sugar beet (Beta vulgaris ssp. vulgaris), ectopic expression of Arabidopsis GRF5 (AtGRF5) in callus cells accelerates shoot formation and dramatically increases transformation frequency. More importantly, overexpression of AtGRF5 enables the production of stable transformants in recalcitrant sugar beet varieties. Similarly, in other organogenesis-based transformation protocols, the introduction of AtGRF5 and GRF5 orthologs into the dicot species soybean (Glycine max L.), canola (Brassica napus L.), and sunflower (Helianthus annuus L.) resulted in significant increases in genetic transformation of the explant tissue. However, significant increases in whole plant regeneration were not found in canola and sunflower, which could be attributed to the cell culture method used in plant regeneration. A positive effect on shoot regeneration via organogenesis in canola was also observed upon overexpression of other Arabidopsis GRF family members, namely AtGRF6 and AtGRF9. Interestingly, in soybean increased transformation was observed in both organogenic and embryogenic-based transformation methods, which resulted in fertile, healthy plants. Additionally, the transformation of two putative AtGRF5 orthologs in maize (Zea mays L.) increased transformation frequency and resulted in fully fertile plants. Overall, the results suggest that overexpression of GRF genes render cells and tissues more competent to regeneration across a wide variety of crop species and regeneration processes. This sets GRFs apart from other developmental regulators and, therefore, they can potentially be applied to improve transformation of monocot and dicot plant species.